Peran Guru dalam Pembelajaran Seni Tari (Rentak Bulian) di SMAN 5 Pekanbaru dalam Menggunakan Kurikulum Merdeka - Annisa Fitria Nuski; Yahyar Erawati (Yayasan Al-Afif, 2025)
This study explores the role of teachers in the learning of Rentak Bulian dance in class XI Engineering 1 at SMAN 5 Pekanbaru using the Merdeka Curriculum approach. The objective of this research is to describe how the teacher implements various roles educator, facilitator, demonstrator, and motivator, in guiding students through traditional dance learning. The method used was qualitative descriptive with data collected through observation, in-depth interviews, and documentation. The findings indicate that the teacher applies active and reflective teaching strategies to support student learning outcomes in the domains of cognitive, affective, and psychomotor. The Rentak Bulian dance learning process integrates local cultural values and fosters student character development. These findings suggest that the Merdeka Curriculum offers flexibility and cultural relevance in arts education. The teacher’s holistic role has a positive impact on students’ performance and appreciation of traditional dance.